Characteristics of miR-1322 interaction with mRNA of genes involved in the development of breast cancer (Experimental biology, 2017)
The work is devoted to finding miR-1322 binding sites in mRNAs candidate genes AFF3, AR, ARID3B, E2F4, NCOA3, NCOR2, SMARCA2, involved in the development of breast cancer. In mRNAs of human AFF3 gene have been identified two binding polysites of miR-1322 encoding polyserines. Three binding polysites of miR-1322 in mRNAs of AR gene encoded polyglutamins. Two binding polysites of miR-1322 in mRNAs of human ARID3B gene encoded two polyglutamine. mRNAs of orthologous NCOA3 genes contained 10 to 15 miR-1322 binding sites. The binding sites of mir-1322 with mRNAs of E2F4 gene encoded polyserin. Orthological genes of NCOR2 encoded polyglutamine, the interaction characteristics of mir-1322 with mRNAs were similar. All miR-1322 binding sites with mRNAs of SMARCA2 gene encoded polyglutamine and had the same interaction characteristics. All miR-1322 binding polypeptides in mRNAs of all orthologous genes were flanked by conserved nucleotide sequences. The binding characteristics of miR-1322 with mRNA of all orthologous genes were close. miR-1322, together with these genes, can be used as markers for early diagnosis of breast cancer and other cancers.
Keywords: miR-1322; mRNA; oncogenesis; breast cancer; orthologous genes.